The Concept of Intention in the Quran and Hadith and Its Implications for Behavior in a Modern Context - Ali Junnifar (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2025)
Intention is a central concept in Islam that determines the quality and value of a deed. This article aims to analyze the concept of intention in depth, from philosophical, psychological, and social perspectives, and its implications for human behavior in the context of modern life. The research method employed is a systematic literature review, which collects data from primary sources, including the Quran, Hadith, and the works of classical scholars, as well as secondary sources such as books, journals, and contemporary research. The analysis shows that intention not only determines the spiritual value of an act but also influences the motivation, quality, and social impact of the act. This article concludes that a deep understanding of the concept of intention can provide an ethical and spiritual foundation for individuals in facing the challenges of modern life, including globalization, materialism, and moral degradation.